IMPLEMENTASI TRANSFORMASI DIGITAL DAN INOVASI PERBANKAN BANK MANDIRI - Lutfi Alfiansyah (2023)
In the context of digitalisation and changes in people's habits that are increasingly digital, banking services are required to accelerate the transformation to digital banking. This Final Project aims to find out the implementation and banking innovation of Bank Mandiri. In this Final Project, the author uses literature study data collection techniques by observing various theories and discussions related to information from various sources such as literature, annual reports, and other necessary information. Bank Mandiri is utilising the pandemic as a momentum to increase transactions and expand the network for its digital banking products. The existence of Livin', Kopra, and Smart Branch has a significant impact on Bank Mandiri's fundraising, especially on low-cost funds and fee-based income levels. Bank Mandiri's performance results in 2022 in continuing digital transformation can be said to be successful as seen from the increasing trend in users, number of transactions, and nominal transactions in each digital service. Bank Mandiri was able to increase the CASA ratio and fee-based income from the previous year.